High-grade focal areas in low-grade central osteosarcoma: high-grade or still low-grade osteosarcoma?. Issue 1 (December 2015) - Righi, Alberto; Paioli, Anna; Dei Tos, Angelo; Gambarotti, Marco; Palmerini, Emanuela; Cesari, Manuela; Marchesi, Emanuela; Donati, Davide; Picci, Piero; Ferrari, Stefano
Abstract Background High-grade foci (grade 3 according to Broder's grading system) are sometimes detected in low-grade (grade 1 and 2) central osteosarcoma. The aim of this study was to retrospectively evaluate the clinical outcome in patients upgraded to high grade (grade 3) after a first diagnosis of low-grade osteosarcoma, following the detection of high-grade areas (grade 3) in the resected specimen. Methods Of the 132 patients with a diagnosis of low-grade central osteosarcoma at surgical biopsy at our Institute, 33 patients were considered eligible for the study. Results Median age was 37 (range 13–58 years). Location was in an extremity in 29 patients (88 %). Post-operative chemotherapy was given in 22 (67 %) patients. Follow-up data were available for all patients, with a median observation time of 115 months (range 4–322 months). After histological revision, areas of high-grade (grade 3) osteosarcoma accounting for less than 50 % of the tumor were found in 20 (61 %) patients, whereas the majority of the tumor was composed of a high-grade (grade 3) component in 13 (39 %) patients. In the 20 cases of low-grade osteosarcoma with high-grade foci (grade 3) in less than 50 % of the tumor, 9 patients did not receive adjuvant chemotherapy; only one of them died, of unrelated causes. In the adjuvant chemotherapy group (11 out of 20 patients), one patient developed multiple lung metastases and died of disease 39 months after the first diagnosis. In the other 13 cases of low-grade osteosarcoma with high-grade foci (grade 3) in more than 50 % of the tumor, 12 patients received adjuvant chemotherapy: 2 had recurrence, 4 developed multiple lung metastases and 3 died of disease. The only patient who did not receive chemotherapy is alive without disease 232 months after complete surgical remission. Conclusion Our data indicate that patients with a diagnosis of low-grade osteosarcoma where the high-grade (grade 3) component is lower than 50 % of the resected specimen, may not require chemotherapy, achieving high survival rates by means of complete surgical resection only.